Complex Interaction Networks Among Cyanolichens of a Tropical Biodiversity Hotspot - Kaasalainen, Ulla; Tuovinen, Veera; Mwachala, Geoffrey; Pellikka, Petri; Rikkinen, Jouko (Frontiers in Microbiology, 2021)
Interactions within lichen communities include, in addition to close mutualistic associations between the main partners of specific lichen symbioses, also more elusive relationships between members of a wider symbiotic community. Here we analyze association patterns of cyanolichen symbionts in the tropical montane forests of Taita Hills, Kenya, a global biodiversity hotspot. The cyanolichen specimens analyzed represent 74 mycobiont taxa within the order Peltigerales (Ascomycota), associating with 115 different variants of the photobionts genus Nostoc (Cyanobacteria). Our analysis demonstrates wide sharing of photobionts and reveals the presence of several photobiont-mediated lichen guilds. Over half of all mycobionts share photobionts with other fungal species, often from different genera or even families, while some others are strict specialists and exclusively associate with a single photobiont variant. The most extensive symbiont network involves 24 different fungal species from five genera associating with 38 Nostoc photobionts. The Nostoc photobionts belong to two main groups, the Nephroma type Nostoc and the Collema/Peltigera type Nostoc, and nearly all mycobionts associate only with variants of one group. Among the mycobionts, species that produce cephalodia and those without symbiotic propagules tend to be most promiscuous in photobiont choice. The extent of photobiont sharing, and the structure of interaction networks differ dramatically between the two major photobiont-mediated guilds, being both more prevalent and nested among Nephroma guild fungi and more compartmentalized among Peltigera guild fungi. This presumably reflects differences in the ecological characteristics and/or requirements of the two main groups of photobionts. The same two groups of Nostoc have previously been identified from many lichens in various lichen-rich ecosystems in different parts of the world, indicating that photobiont sharing between fungal species is an integral part of lichen ecology globally. In many cases symbiotically dispersing lichens can facilitate the dispersal of sexually reproducing species, promoting establishment and adaptation into new and marginal habitats and thus driving evolutionary diversification.